2022
DOI: 10.13189/saj.2022.100607
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Anxiety Level of International and National Kurash Athletes before and during Competition

Abstract: The anxiety of an athlete in the process of participating in competitions and in the process of competitions is the main obstacle to achieving sports results. This study aimed to compare the state of anxiety before and during the competition of different levels and gender categories of kurash athletes. A total of 450 kurash athletes (international level -225, national level -225, males -238, females -212) voluntarily participated in this study. The verification of participants was carried out at 4 competitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
0
0
Order By: Relevance
“…The study depended on several factors and it concluded that gender had no significant effect on the anxiety level of the athletes. Furthermore, this study had also previously determined the competitive anxiety level of international and national kurash athletes before and during the competition [20].…”
Section: Discussionmentioning
confidence: 99%
“…The study depended on several factors and it concluded that gender had no significant effect on the anxiety level of the athletes. Furthermore, this study had also previously determined the competitive anxiety level of international and national kurash athletes before and during the competition [20].…”
Section: Discussionmentioning
confidence: 99%